2009
DOI: 10.1007/s11605-008-0610-z
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Strangulated Small Bowel Obstruction: An Old Problem Revisited

Abstract: Regression analysis of multiple preoperative criteria demonstrates that reduced wall enhancement on CT, peritoneal signs, and elevated WBC are the only variables independently predictive of bowel strangulation in patients with SBO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 17 publications
3
72
0
2
Order By: Relevance
“…6 Failure to predict strangulation early among these patients often delays surgical intervention there by leaving a significant impact on the outcomes. On history strangulation can be predicted among patients presenting with small intestinal obstruction based on delayed presentation beyond 72 hours with continuous abdominal pain, bleeding per rectum or blood stained aspirate in the nasogastric tube and with high grade fever.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Failure to predict strangulation early among these patients often delays surgical intervention there by leaving a significant impact on the outcomes. On history strangulation can be predicted among patients presenting with small intestinal obstruction based on delayed presentation beyond 72 hours with continuous abdominal pain, bleeding per rectum or blood stained aspirate in the nasogastric tube and with high grade fever.…”
Section: Discussionmentioning
confidence: 99%
“…5 Identification of defined clinical criteria predictive of strangulation among patients with small bowel obstruction will allow an early decision making regarding exploratory laparotomy and thereby can lead to improved outcomes. 6 Several laboratory parameters which can predict strangulation like serum amylase, serum lactate, serum LDH have been investigated though none of them have been proved to be neither sensitive nor specific. Imaging wise only CT scan has been proved to be of some value in the detection of strangulation among patients with small bowel obstruction but most often it is not a readily available investigation and it often predicts strangulation only after irreversible ischemia has already set in.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, radiologists sometimes encounter cases in which the diagnosis of strangulation is very difficult; this situation is certainly not uncommon in clinical practice. Of interest, Jancelewicz et al (6) recently investigated 72 preoperative clinical, laboratory, and radiologic (CT) findings in 192 patients who presented with SBO, and reported that reduced bowel wall enhancement was the most significant independent predictor of bowel strangulation. However, although specificity of this CT sign was 94%, sensitivity was only 56% (6).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, Jancelewicz et al (6) recently investigated 72 preoperative clinical, laboratory, and radiologic (CT) findings in 192 patients who presented with SBO, and reported that reduced bowel wall enhancement was the most significant independent predictor of bowel strangulation. However, although specificity of this CT sign was 94%, sensitivity was only 56% (6). Thus, the diagnosis of strangulation remains a challenge even when using CT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation